Note—A Note on Goal Decomposition in a Decentralized Organization - Freeland, James R. (Management Science, 1976)
The purpose of this note is to show that Ruefli's Generalized Goal Decomposition Model does not allow one to interpret the solution routine as a decentralized process with respect to information processing and decision making. It is then shown how the application of a partitioning algorithm within Ruefli's framework can overcome these interpretation shortcomings.